POLITICAL BUDGET IN ARRANGING LOCAL INCOME AND EXPENDITURE BUDGET OF SUNGAI PENUH TOWN IN 2012 - Helmi Helmi; Aidinil Zetra; Rice Trisnawati (Centre for Asian Social Science Research (CASSR), FISIP, UIN Bandung, 2019)
Budgeting process is a political activity that is the monitoring tool for society toward government. This process will involve various elements which have an interest in the budget arranging process. They are not only Executive element, but also Legislative. The purpose of this research is to analyze the dynamics of Allocation Budget Contestation of Direct Expenditure in Arranging Local Income and Expenditure Budget (APBD) of Sungai Penuh Town in 2012. This research is descriptive research by using a qualitative approach. The location is chosen to help the researcher to understand the problem of research. The location is determined purposely and based on the problems that happened in the field that related to Political Budget in Arranging Local Income and Expenditure Budget process of Sungai Penuh Town in 2012. The Location is in the Government of Sungai Penuh Town and around the society. Triangulation technique is chosen in this research because it uses some data from interview and documentation. According to Principal and Agent Theory, there are 4 stages in the budgeting process. They are Executive planning, Legislative Approval, Executive Implementation, and Ex-pose Accountability. Based on the result of this research, Dynamics of Allocation Budget Contestation of Direct Expenditure in Local Income and Expenditure Budget of Sungai Penuh Town are: 1) there is a Mutual Coordination Relationship between Executive and Legislative in Arranging Local Income and Expenditure Budget process. It stars from composing General Budget Policies–Provisional Budget Priorities and funding Level (KUA-PPAS) and Integrated Work Plan and Budget (RKA) and the agreement between Mayor and Sungai Penuh Legislative. 2) In interdependence, there are political domination and transaction among institutions in arranging until determining Local Regulation. Domination is between Executive and Legislative. 3) Negotiation (Lobbying) evidence in Executive and Legislative relationship. Legislative doesn’t have an authority to make work plan, but Legislative can change the budget even they can change the program that they want. It makes negative negotiation happens.